The impact of leadership churn on quality management in Australian hospitals. Issue 7 (7th November 2019) - Leggat, Sandra; Balding, Cathy
Abstract : Purpose: The purpose of this paper is to explore the relationship between frequent turnover (churn) of the chief executive officer (CEO), quality manager and members of the governing board with the management of quality in eight Australian hospitals. Design/methodology/approach: A mixed method three-year longitudinal study was conducted using validated quality system scales, quality indicators and focus groups involving over 800 board members, managers and clinical staff. Findings: There were unexpected high levels of both governance and management churn over the three years. Churn among CEOs and quality managers was negatively associated with compliance in aspects of the quality system used to plan, monitor and improve quality of care. There was no relationship with the quality of care indicators. Staff identified lack of vision and changing priorities with high levels of churn, which they described as confusing and demotivating. There was no relationship with quality processes or quality indicators detected for churn among governing board members. Practical implications: Governing boards must recognise the risks associated with management change and minimise these risks with robust clinical governance processes. Originality/value: This research is the first that we are aware of that identifies the impact of frequent leadership turnover in the health sector on quality management.